A new time-frequency domain simulation method for damage accumulation and life prediction of composite thin-wall structures under random cyclic loadings. (1st February 2022) - Wu, Zengwen; Zhang, Zhenya; Wu, Jianguo; Liang, Jun; Ge, Jingran; Liu, Xiaoli; Fang, Guodong
Abstract: A time-frequency domain simulation method has been developed to predict the lifetime and simulate the damage evolution of composite thin-wall structures subjected to random fatigue loading. Simulation method contains two main parts: (1) structural response based on the power spectral density loading, and (2) damage progression according to residual stiffness model of material. Simulation is proceeded based on step-by-step update of material properties in time domain. For each step fundamental frequency is calculated to determine the degradation ratio of frequency. Time corresponding to the critical degradation ratio of frequency is defined as the lifetime. The method presented in this paper presents a possible solution for practical engineering applications of composite thin-wall structures subjected to the random fatigue loadings and can be applied to other similar thin-wall structure with more complex features.